1985
DOI: 10.1042/bj2310439
|View full text |Cite
|
Sign up to set email alerts
|

Elevated hepatic mitochondrial and peroxisomal oxidative capacities in fed and starved adult obese (ob/ob) mice

Abstract: Hepatic mitochondrial and peroxisomal oxidative capacities were studied in young (4-5 weeks old) and adult (6-9 months old) lean and obese ob/ob mice that were fed or starved for 24 or 48 h. The adult obese mice showed elevated capacity for mitochondrial oxidation (ng-atoms of O consumed/min per mg of protein) of lipid and non-lipid substrates, with the exception of pyruvate + malate, and elevated activities of citrate synthase and total carnitine palmitoyltransferase. Oxidative rates and enzyme activities wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 36 publications
10
56
0
Order By: Relevance
“…1 Other studies showed that hepatic mitochondria from adult obese mice exhibit elevated capacity to oxidize nonlipid substrates. 2,52 This supports the notion that hepatic mitochondria from obese mice have an increased capacity to metabolize reducing equivalents, whether they are NAD þ -or FAD-linked. They also show elevated specific activity of CS and elevated capacity for mitochondrial and peroxisomal oxidation of lipid substrates.…”
Section: Effect Of Agesupporting
confidence: 70%
“…1 Other studies showed that hepatic mitochondria from adult obese mice exhibit elevated capacity to oxidize nonlipid substrates. 2,52 This supports the notion that hepatic mitochondria from obese mice have an increased capacity to metabolize reducing equivalents, whether they are NAD þ -or FAD-linked. They also show elevated specific activity of CS and elevated capacity for mitochondrial and peroxisomal oxidation of lipid substrates.…”
Section: Effect Of Agesupporting
confidence: 70%
“…In obesity and steatosis, increased fatty acid metabolism leads to increased mitochondrial respiratory activity and excessive production of mitochondrial reactive oxygen species (ROS) in the liver, 8,28 which are known to regulate T-cell apoptosis. 29 High levels of ROS probably kill cells directly, whereas low levels probably mediate apoptosis indirectly through their effects on signal transduction and gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…17 Theoretically, it is possible that all of these mechanisms are present and participate in the increase in myocardial lipid peroxidation in obesity. Nonetheless, to date, there is no experimental evidence regarding which of these mechanisms are contributors to the myocardial oxidative damage associated with obesity.…”
Section: Introductionmentioning
confidence: 99%